Pancasila Sebagai Dasar Negara dan Implementasinya dalam Berbagai Bidang - Alvira Oktavia Safitri; Dinie Anggraeni Dewi (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
This paper is aims to identify and explain about the implementation of Pancasila as the basis of the state in maintaining the existence of the Indonesian nation. The research method uses a qualitative study approach of descriptive approach where the discussion is obtained from the results of literature studies on book sources, relevant journals that that have been there before, and articles. The research results show an overview of the implementation of the values contained in the Pancasila principles in maintaining the existence of the nation, the meaning of each Pancasila precepts, along with functions and functions of the pancasila as the basis of the Indonesian state.In this case, Pancasila has a very important role for the Indonesian people, in advance of the current creation so that it can be implemented in everyday life, with the hope of creating a successor who can always maintain the existence of the Indonesian nation.